An analysis of the factors affecting preferences for rental houses in istanbul using mixed logit model a comparison of european and asian side - GÜRİŞ, SELAHATTİN (My University, 2016)
This study aims to analyze the factors affecting households’ preferences to select houses for rent in Asian and European side of Istanbul with Mixed Logit model. Analysis showed that earthquake resistance, luxury, proximity to hospital, presence of green areas, luxury-comfort level positively affected the preferences for houses for rent of households residing in European side, while monthly rent when compared to the present house negatively affected their preferences. As for the Asian side, monthly rent and tiring effect of working time negatively affected house preferences, while proximity to city center, size of the house, presence of green areas and proximity to educational facilities positively affected the preferences for houses for rent.
Keywords: Sosyal ve Beşeri Bilimler; Ekonometri; Social Sciences and Humanities; Econometrics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; Housing preferences; Mixed logit model; Rental housing; Revealed Preference; Stated Preference